2020
DOI: 10.1371/journal.pone.0239162
|View full text |Cite
|
Sign up to set email alerts
|

Player load in male elite soccer: Comparisons of patterns between matches and positions

Abstract: Our primary aim was to explore the development of player load throughout match time (i.e., the pattern) using moving 5-min windows in an elite soccer team and our secondary aim was to compare player load patterns between different positions within the same team. The dataset included domestic home matches (n = 34) over three seasons for a Norwegian Elite League team. Player movements (mean ± SD age 25.5 ± 4.2 years, height 183.6 ± 6.6 cm, body mass 78.9 ± 7.4 kg) were recorded at 20 Hz using body-worn sensors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The total distance covered was monitored in 13 of the 17 studies included in this systematic review. This finding confirms that the total distance covered is, historically, one of the first variables to be monitored and the most commonly used variable for measuring external load in many sports [ 51 , 52 , 53 , 54 ]. Our results show that an elite handball player covered an average of 3664.4 ± 1121.6 m during a match (from 1346.6 ± 3852.5 to 6943.9 ± 364.4 m).…”
Section: Discussionsupporting
confidence: 73%
“…The total distance covered was monitored in 13 of the 17 studies included in this systematic review. This finding confirms that the total distance covered is, historically, one of the first variables to be monitored and the most commonly used variable for measuring external load in many sports [ 51 , 52 , 53 , 54 ]. Our results show that an elite handball player covered an average of 3664.4 ± 1121.6 m during a match (from 1346.6 ± 3852.5 to 6943.9 ± 364.4 m).…”
Section: Discussionsupporting
confidence: 73%
“…Physical competition characteristics vary by playing position, depending on a number of situational factors, including tactical decisions, team formation, opponents style of play and level of competition [ 159 , 160 ]. Total distance during a professional men’s match ranges from 10 to 12 km, with central midfielders covering the highest distance (11,885 m) while central defenders and strikers cover the lowest (10,671 m and 10,790 m, respectively) [ 161 ].…”
Section: Sport Specific Analysismentioning
confidence: 99%
“…11 However, this pattern was not observed for other external load variables such as distance covered, sprinting distance, total accelerations, or total decelerations. 11 This is also consistent with other investigations, which observed that playing position had no significant effect on the locomotor efficiency (ie, PL TOTAL per meter covered) 28 and that the variance in the PL TOTAL was not significantly explained by the positional role during elite soccer match play. 1 Nevertheless, other researchers also showed that positional differences in PL TOTAL may exist across playing positions.…”
Section: Discussionmentioning
confidence: 88%
“…In this regard, a recent study observed that the pattern of development of the PL TOTAL , PL V , PL ML , and PL AP throughout match time was very similar in all playing positions, which implies that physical pacing patterns might be employed by soccer players. 11 However, this pattern was not observed for other external load variables such as distance covered, sprinting distance, total accelerations, or total decelerations. 11 This is also consistent with other investigations, which observed that playing position had no significant effect on the locomotor efficiency (ie, PL TOTAL per meter covered) 28 and that the variance in the PL TOTAL was not significantly explained by the positional role during elite soccer match play.…”
Section: Discussionmentioning
confidence: 88%